Barriers and facilitators to primary healthcare utilization among immigrants and refugees of low and middle-income countries: a scoping review - Seyed Mohammad Iman Moezzi; Manal Etemadi; Kamran Bagheri Lankarani; Masoud Behzadifar; Hamidullah Katebzada; Saeed Shahabi (BMC, 2024)
Abstract Introduction Primary health care (PHC) is the most common model for providing primary care, and PHC services are the most common points of care that immigrants and refugees attend as a first step. Most immigrants travel to low- and middle-income countries (LMICs), yet only a few studies have examined their health conditions and their access to PHC in these countries. We have attempted to identify the barriers and facilitators that immigrants and refugees encounter when using PHC in these countries. Methods We searched PubMed, Scopus, Web of Science, Embase, ProQuest, Google Scholar, Microsoft Academic, and OpenGrey in this scoping review from its inception to the end of October 2023. Moreover, we manually searched key journals, reference lists, and citations from included studies to identify any missed studies. We extracted data from each selected study using a predefined form. Finally, a thematic analysis approach was utilized to synthesize the collected data from the included qualitative studies. Results 17 qualitative studies were included in this review, which were from Iran (n = 3), Brazil (n = 3), Kenya (n = 2), Jordan (n = 2), Eastern Sudan (n = 1), Lebanon (n = 1), Bangladesh (n = 1), India (n = 1), Turkey (n = 1), Thailand (n = 1), and Malaysia (n = 1). Among the most common and important reported barriers are language differences, insufficiency of trained carers, unemployment, inability to pay the costs of hospital and medicines, no insurance coverage for immigrants, no clear referral and care system for immigrants, discrimination against women, and improper residence locations. Insurance coverage, awareness programs, and the study of immigrants' needs, along with their social and financial support from family, are among the most essential facilitators. Conclusion For LMICs, funding is always a limitation, and increasing PHC utilization is the best choice for improving health. Knowing the challenges and facilitators of PHC utilization from the point of view of each stakeholder is a promising way to decide and make policies that can improve the health of both immigrants and refugees, as well as society as a whole.